(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The purpose of this study was to investigate the challenges that students in the 11th gradeface when attempting to understand probability ideas. In order to accomplish this objective, ten distinctopen-ended probability difficulties were presented to the 170 students in the 11th grade. Each of theseissues calls for the application of a unique set of fundamental probability theories. It is qualitative study,and the descriptive method was used to analyse the information that was collected in this investigation.According to the observations, a significant number of these students struggled to find solutions toproblems involving probability and were unable to successfully apply various theories of probability tothese troubles. It should be noted that it was asserted that a number of students had difficulty locatingall of the probabilities in these concerns without any of them being missing. In addition, it is crucial toimprove reasoning skills because students usually use the technique of trial and error in conjunctionwith forecasting in order to solve issues involving probability.